2020
DOI: 10.1371/journal.pone.0226324
|View full text |Cite
|
Sign up to set email alerts
|

Determining the cut-off score for the Modified Barthel Index and the Modified Rankin Scale for assessment of functional independence and residual disability after stroke

Abstract: Assessment of functional independence and residual disability is very important for measuring treatment outcome after stroke. The modified Rankin Scale (mRS) and the modified Barthel Index (MBI) are commonly used scales to measure disability or dependence in activities of daily living (ADL) of stroke survivors. Lack of consensus regarding MBI score categories has caused confusion in interpreting stroke outcomes. The purpose of this study was to identify the optimal corresponding MBI and modified Rankin scale (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 31 publications
1
56
0
2
Order By: Relevance
“…Further, he suggested that a BI score ≧90 with mRS ≦2 to be the optimal cutoff score to define a favorable outcome (sensitivity: 90.7%, specificity: 88.1%) [ 16 ]. Recently, a study of 5,759 stroke patients found the optimal cutoff points of the Korean versions of the MBI (K-MBI) to be 98 (sensitivity: 90.4%; specificity 83.8%) and 94 (sensitivity: 88.5%; specificity: 93.7%) for mRS grades 1 and 2, respectively [ 19 ]. Our preliminary study found the optimal cutoff scores of BI to be 100 (sensitivity: 100%; specificity 95.3%) and 100 (sensitivity: 98.1%; specificity 100%) corresponding to the adjusted mRS 1 and 2, respectively [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, he suggested that a BI score ≧90 with mRS ≦2 to be the optimal cutoff score to define a favorable outcome (sensitivity: 90.7%, specificity: 88.1%) [ 16 ]. Recently, a study of 5,759 stroke patients found the optimal cutoff points of the Korean versions of the MBI (K-MBI) to be 98 (sensitivity: 90.4%; specificity 83.8%) and 94 (sensitivity: 88.5%; specificity: 93.7%) for mRS grades 1 and 2, respectively [ 19 ]. Our preliminary study found the optimal cutoff scores of BI to be 100 (sensitivity: 100%; specificity 95.3%) and 100 (sensitivity: 98.1%; specificity 100%) corresponding to the adjusted mRS 1 and 2, respectively [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patient health questionnaire (9 and PHQ-9), modified Barthel (MBI) Patient Health Questionnaire-9 was a measure of depression and >4 diagnosed depression ( Levis et al, 2019 ). MBI is a common scale to measure daily living disability or dependence in stroke patients ( Lee et al, 2020 ), 0–100, the lower the score indicates the poor living ability At 1d before treatment and 8 weeks after treatment, the 5 ml, blood collection site of the two groups was fasting venous blood before the elbow, 1d, of serum was static placed at room temperature after anticoagulant, and the serum was taken for-80℃ freezing in the medical refrigerator The HPLC method is used ( Hirowatari and Yoshida, 2019 ). Determination of the patient serum monamines and amino acid neurotransmitters, including dopamine (dopamine, DA), norepinephrine (norepinephrine, NE), 5-serotamine (5-hydroxytruptamine,5-HT) and amino acid neurotransmitters including glutamate (glutamatem, Glu) and glycine (glycine, Gly).…”
Section: Methodsmentioning
confidence: 99%
“…Then, cognitive ability and functional capacity were assessed with the Montreal Cognitive Assessment (MoCA) [ 30 ] and the modified Rankin Scale (mRS) [ 31 ], respectively. Regarding the latter, most stroke trials define a favorable functional outcome as mRS grade ≤2 [ 32 ]. Therefore, we rated participants who scored ≤2 as “No disability or slight” and those who scored 3 to 5 as “Moderate or severe disability”.…”
Section: Methodsmentioning
confidence: 99%